Resseguro e desenvolvimento: entre estado e mercado, lei e contrato - Dias, André Orengel (2011)
In order to verify the relationship between models of development predominantly adopted, Constitutional Economic Law and regulation of reinsurance activity in Brazil, the present work studies the changes perpetrated on the use of claims handling clauses in reinsurance contracts in specific moments of Brazilian history, when intense reforms caused important changes in the models of regulation and development in this country: the Vargas era, the Castelo Branco presidency and the Fernando Henrique Cardoso presidency. To carry out this task, the present study, first and foremost, examines the reasons that led to the monopolization and the insulation of the national reinsurance sector along with the creation of Brazilian Reinsurance Institute (BRI) in 1939 and establishes its relationship with the model of development implanted after the 1930 Revolution, the transition from liberal to social Law and the Economic Law confined in the 1934 and 1937 Constitutions. Hereinafter, these facts are weighed against the rules that started to regulate the contracts signed between the BRI and the national insurance companies, specifically those that refer to claims handling. Next, the evolution of the reinsurance market regulation, the creation of the Private Insurance National System and the monopoly of the BRI over this activity are analyzed against its interaction with the models of development that guided the role played by the Brazilian State in the following decades and the Economic Law introduced into the 1946, 1967 and the 1988 Constitutions. After, the uses of claims handling clauses in the reinsurance contracts signed by the BRI under the ruling of the Decree number 73/66 are analyzed through the examination of the Retrocession and Reinsurance General Norms (RRGN) and the Retrocession and Reinsurance Specific Norms (RRSN), both enacted by the BRI. In the first chapter of its second part, this work verifies the relation between the neo-liberalism of the 1980’s and 1990’s, the social solidarity constitutional directive and the good-faith principle in order to comprehend how the changes in the constitutional text made in the 1990’s and the 2000’s altered the negotiation of reinsurance contracts in Brazil. This is aimed at clarifying the correlation between the de-monopolization and the opening of the Brazilian reinsurance activity, the current Constitutional Economic Law and the announced change in the development strategy implemented by the Brazilian government. In order to understand how private corporations started behaving in the recently opened market, the preset dissertation investigates the use of claims handling clauses in reinsurance contracts through the analysis of collected answers to given questionnaires, Brazilian and foreign doctrine on the matter and reinsurance standard contracts in use nowadays. In this same chapter, the possible changes on the comprehension of the international character of the reinsurance activity will also be examined in order to determine the current importance of the international customs as a hermeneutic model and an evidence of a general practice accepted as law. Finally, this work studies the rules proposed by the Bill nº 2.555/2004 and its Substitutes about the use of claims handling clauses in reinsurance contracts. At this moment, some alternative writings of the articles examined are suggested, in addition to some points to be considered in order to define the amplitude of the freedom to contract those clauses granted to the parties.